Linear polymerization shrinkage of Bulk Fill resins (Revista da Faculdade de Odontologia - UPF, 2018)
AbstractObjective: the objective of the present study was to analyze the polymerization shrinkage gap of different composite resins. Methods: four commercial brands (n=5) were tested: Z350 (3M/ESPE); Filtek Bulk Fill (3M/ESPE); Surefill (Dentsply); Xtra Base (Voco). Increments of composite resins were inserted into a circular metal matrix of 7 mm internal diameter and 4 mm high and pressed by two glass plates supported on polyester strips. After photoactivation with a Optilight Plus device (Gnatus), with light intensity of 1000 ± 10mW/cm2, the test samples were polished and 24h later, taken to the scanning electron microscope for analysis of the polymerization shrinkage gap, measured at 4 points in the sample (3, 6, 9, and 12 o’clock). The data were analyzed by analysis of variance (Anova one-way). Results: the highest mean of polymerization shrinkage gap was observed for Filtek Z350 (3M/ESPE), while the lowest mean of gap was found for Xtra Base (Voco) brand, with significant differences between the groups. Conclusion: the inorganic filler content and different associations in the organic matrices interfered expressively in the polymerization shrinkage gap. Keywords: Composite resins. Bulk Fill resins. Polymerization shrinkage.